Study Komparatif Penambahan Zat Aditif Alami Dan Kimia Sintetis Pada Pertamax dalam Mengurangi Emisi Gas Buang Kendaraan Bermotor - Nanang Okta Widiandaru; Arif Novianto; Rifkqi Jinan Albadi (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2026)
The emergence of Pertamax Green 95 in 2023, with the specification of a bioethanol blend in Pertamax resulting in an octane value of 95, is expected to be a better fuel than Pertamax in terms of vehicle performance and lower exhaust emissions. To confirm this hypothesis, research is needed to determine the comparison of using Pertamax, Pertamax Green (Pertamax mixed with bioethanol/natural additive), and a mixture of Pertamax with an octane booster/synthetic chemical additive on exhaust emissions. The researchers will use the experimental method for this study. The purpose of experimental research is to determine the results of a study due to several treatments or actions taken by the researchers. The research object uses carburetor and EFI cars with Pertamax, Pertamax Green 95, and a mixture of Pertamax and Octane Booster as fuel. The comparison of using Pertamax, Pertamax Green 95, and a mixture of Pertamax with Octane Booster shows significant differences in emissions, which also vary for each vehicle. The lowest emission content in carbureted vehicles was found in Pertamax Green 95 fuel, with an average CO content of 8.76% and an average HC content of 3347.78 ppm. Meanwhile, the lowest emissions in EFI vehicles were also found with Pertamax Green fuel, with an average CO and HC emission content of 0.013% and 5.06 ppm, respectively. Statistical testing was conducted using the Kruskal-Wallis test on the three fuels, yielding significance values (Asymp. Sig.) for CO levels of 0.02 for the carburetor and <0.001 for the EFI, while HC levels were <0.001 for both the carburetor and the EFI. It was concluded that there are significant differences between the three fuel groups in the exhaust gas emission test results.